Diagnostic Role of Adenosine Deaminase (ADA) among Tuberculous Meningitis Patients (Bangladesh Journal of Neuroscience, 2013)
Background: In the developing countries where TB is endemic; an ideal test for tuberculous meningitis should be economic, minimally invasive, of high accuracy and quick to perform.In many countries, also in India, several studies were conducted to establish the ADA activity as a sensitive and specific test of tuberculous meningitis.So it is very much needed to evaluate the diagnostic role of CSF ADA in tuberculous meningitis in Bangladesh.Aim: This study aimed to find out CSF ADA as a sensitive and specific test for early diagnosis of tuberculous meningitis.Methods: This case control study was carried out in the Department of Neurology, SSMC and Mitford Hospital, Dhaka from June 2011 to July 2012, to evaluate ADA activity in CSF for diagnosis of tuberculous meninigitis.Results: In the present study, sixty meningitis patients were enrolled. Of which, 30(50%) were tuberculous meningitis (TBM) taken as cases and rest 30(50%) were non-tuberculous meningitis (NTBM) taken as control.The CSF ADA activity from TBM patients was compared with CSF ADA from non-TBM infectious meningitis patients. The mean CSF ADA activity was found to be significantly higher in CSF of TBM patients, 14.01 ± 12.4 (1.0–65.2), mean ± SD with range, than in the CSF from non-TBM infectious meningitis, 7.2 ± 8.2 (1.8–49.1) P = 0.01.A cut-off value of >7.6 U/L for the TBM patients was calculated from the mean ±SD of the non-TBM patients.The ADA sensitivity is 81.82%,specificity 65.31%,accuracy 68.33%, PPV 34.62%,NPV 94.12%, positive likelyhood ratio 2.3 and lastly negative likelyhood ratio 0.2 for infectious TBM when this cut-off value was used.ROC curve shows area under curve of .736 suggests a moderate accuracy of the test in detection of tuberculous meningitis.Conclusion: This study demonstrated that ADA activity in the CSF of TBM patients, using a cut off value 7.6 U/L, can be useful for the early differential diagnosis of TBM. This test can be performed in any pathology laboratory where more sophisticated methods are not available.Bangladesh Journal of Neuroscience 2013; Vol. 29 (2) : 79-87